Method for determination of varietal purity (typicality), hybridity, sterility of seed lots based on the establishment of the quantitative ratio of alleles of DNA markers - Ж. В. Вдовиченко; В. Г. Спиридонов; С. В. Хомутовська; М. Ф. Парій (Plant Varieties Studying and Protection)
Purpose. To develop a conceptually new method for determination of varietal purity (typicality), hybridity, sterility of seed lots. Methods of molecular biology (genomic DNA extraction, PCR with SSR markers application, capillary electrophoresis), genetic, statistical, mathematical analysis. Results. New method for determining the varietal qualities of seed lot was developed that consists of the following steps: simultaneous DNA extraction from a representative sample of aggregated seeds; PCR and further analysis of the amplification products by determination of the qualitative and quantitative composition of SSR-markers’ alleles; calculation of values of varietal seed lot quality using experimentally derived allele ratios. Conclusions. The developed method for determining varietal qualities of seed lots allows to reduce significantly the consumption of materials, time and labor during the analysis. Consistent qualification and quantification of alleles in the total sample of a seed lot is a conceptually new approach to establish varietal purity (typicality), hybridity, sterility.